The Influence of Service Quality and Customer Satisfaction on Customer Loyalty at the Center for Weather Modification Technology - Adi Bayu Rusandi; Arif Haryana; Nurminngsih (LPPM Universitas Respati Indonesia, 2024)
This study aims to determine the effect of service quality on customer satisfaction. the influence of service quality on customer loyalty and the influence of customer satisfaction on customer loyalty. The object of the research is that there are customers of the Center for Weather Modification Technology. The research sample was 104 respondents, but only 77 respondents responded. Analysis tool using Smart PLS. The results of the study are that service quality has a significant positive effect on customer satisfaction, service quality has a significant negative effect on customer loyalty, and customer satisfaction has a significant positive effect on customer loyalty. Also found that service quality will further enhance customer loyalty when supported by customer satisfaction. Keywords : Marketing, Service Quality, Customer Satisfaction, Customer Loyalty